Inflammatory and immuno-reactivity in mice induced by intramuscular implants of HSNGLPL peptide grafted-polyurethane. Issue 10 (22nd February 2016) - Xiao, Jiangwei; Huang, Cao; Shi, Dandan; Zhu, Rong; Gu, Ruicai; Wang, Huan; Wu, Gang; Liao, Hua
Abstract : Synthetic peptide-based polyurethanes (PUs), introduced as bioactive agents and possessing impressive properties, have emerged as attractive functional biomaterials for tissue regeneration. Abstract : Synthetic peptide-based polyurethanes (PUs), introduced as bioactive agents and possessing impressive properties, have emerged as attractive functional biomaterials for tissue regeneration. In this study, we developed a PU with a pendent HSNGLPL group through click reaction, which has strong affinity to TGF-β1. The peptide grafted-PUs, or PUs with BDO as the chain extender (control), were implanted into the gastrocnemius muscle (GN) of C57BL/6 mice, for evaluating their inflammatory and immuno-reactivity in vivo . We show herein that, after muscle implantation, BDO-PU induced a conspicuous monocyte/macrophage infiltration and myofiber degeneration. The inflammatory invasion and myofiber necrosis were mainly detected in the site around, but not far from, the implants, suggesting that the degraded PU matrix only triggers a local and limited inflammation in vivo . In contrast, peptide grafted-PU induced intramuscular inflammation was more complex and was sustained for more than 2 months. Apart from nonspecific monocyte/macrophage infiltration as in the case of BDO-PU, CD4 + T cells and dendritic cells (DCs), the members of the adaptive immune system, can be detected within the inflammatory site around peptide grafted-PU implants. The number of apoptotic macrophages in muscle containing peptide-PU was significantly lower compared to that in muscle containing BDO-PU. Thus, our present results suggest that, the PU matrix degradation-produced local environment is toxic to muscle cells and induces muscle degeneration. Moreover, highly aggregated peptide on PU might act as an immunogen to trigger intramuscular inflammation and lead to the delayed inflammatory response.